Estudio de pre-factibilidad para la instalación de una planta productora de filtrantes de maíz morado para el mercado local - Pickman Sánchez, Selem (2016)
This study seeks to determine the commercial, technical, economic and social viability of installing a filter production plant of purple corn to the Lima market, using the tools and knowledge learned throughout the career. The product will be called "Runakay" and sold in boxes of 25 sachets. The target market consists of the segment A - B of Lima, all ages and both sexes. According to the study, it is planned by 2020 an amount of 876,466 boxes of purple corn filters sold at a sale value to distributors (supermarkets) of S/. 3,70 each unit and S/ .6,06 to the final consumer.